The Possibilities and Limits of Personal Agency: The Walmart that Got Away and Other Narratives of Food Acquisition in Rural Texas. (2nd January 2016) - Dean, Wesley R.; Sharkey, Joseph R.; Johnson, Cassandra M.
Abstract: The food environment poses many challenges to low-income rural residents as they struggle to sustain themselves and their families. Rural settings in the United States are characterized by poorer food access and availability, including costlier and lower-quality produce, in comparison with urban settings. The practices employed by low-income residents to cope with these rural food environments have nutritional consequences and sometimes even broader health implications. However, these practices can also be interpreted as acts of creative agency. Using insights from earlier work on the environmental determinants of food-related behaviors, and a sociological perspective on the role of individual agency in the process of structuration, this research categorizes food-related hardships, acquisition strategies, and resources, and demonstrates how food access is negotiated within the more or less flexible constraints of rural settings characterized by the unavailability of inexpensive, high-quality foods.